Perancangan Model Balancing Robot untuk Sarana Transportasi Tenaga Medis - M Munadi; Mochammad Ariyanto; Royyan Saputra; Joga D Setiawan (Jurnal Teknik Mesin Indonesia, 2018)
Robots have become mechanical equipment that can perform physical tasks, either by monitoring or using predefined programs (artificial intelligence). One type of robot is a mobile robot that has a driving mechanism in the form of a wheel and leg so that it can move from one place to another. One type of mobile robot includes balancing a two-wheeled robot and can balance itself to the surface of the earth. In this study, we will try to design a model of balancing robots that in future development can be used in hospitals by medical personnel as an environmentally friendly means of transportation. This is because medical personnel often have to be mobile in monitoring patients. Related to this, so that the model of balancing robot can be balanced, one type of controller is used. The sensor used is the NI myRIO accelerometer sensor to detect angular changes, and the gyroscope sensor to detect angular velocity. In order to balance the model of balancing robot, the Proportional-Integral control method is used to adjust the speed of the DC direction of the rotating motor. Tuning Proportional- Integral control parameters is done by two methods, namely Ziegler-Nichols method and trial and error. The good tuning from Proportional Integral is the gain value Kp = 5 and Ki = 0.001.